PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PELAJARAN IPA KELAS V SDN NGALE 01 - Dewan Laser Karisma; Nur Samsiyah; Sunarti (STKIP Subang, 2023)
This study aims to explore the application of the Problem Based Learning (PBL) Model to increase student learning activeness in Natural Sciences (IPA) lessons in class V SDN Ngale 01. The PBL method involves students in solving real problems that are relevant to the context of everyday life, thereby encouraging active engagement and better understanding of concepts. This study used a quantitative approach with a pretest-posttest control group research design. The research sample consisted of two randomly selected classes, namely the experimental class that applied the PBL model and the control class that applied conventional learning methods. Data on student activeness was collected through observation and statistical analysis was used to compare differences in active learning between the two groups. The results showed that the application of the PBL Model significantly increased students' active learning in science lessons. Students who engage in the PBL Model show more active participation in learning, including group discussion, problem solving, and critical thinking. They also showed greater interest in science lessons and the ability to relate concepts to real situations.This research has important implications for education practitioners and science teachers in elementary schools in increasing student learning engagement. The PBL model can be used as an alternative effective learning method to encourage student participation and a deeper understanding of concepts. Future research can involve a larger sample and see the impact of applying the PBL Model on student learning outcomes as a whole.